Forests and Society: Sustainability and Life Cycles of Forests in Human Landscapes - Vogt, K.A (CABI, 2014)
This book aims to provide a ‘road map’ to identify what factors need to be considered when making decisions regarding forest uses, when those uses are excessive and when they have become detrimental. It also attempts to document and clarify the complexity of issues involved in managing forests. This book provides a framework for the general public, forest managers and policymakers to understand what factors need to be included when working towards using and protecting the world’s forests so that they can be sustained.